Influence of Internal Controls, HR Quality, IT, and Accrual Accounting on Financial Report Quality in Central Kalimantan's Religious Courts - Sosilawati, Maya; Kadir, Kadir; Sarwani, Sarwani (Ilomata International Journal of Tax and Accounting, 2025)
This study aims to analyze the influence of internal control systems, quality of human resources, utilization of information technology, and implementation of accrual-based government accounting standards on the quality of financial reports of Religious Courts throughout Central Kalimantan. The findings indicate that the Internal Control System is the most dominant factor (coefficient 0.327) in influencing the Quality of Financial Reports of Religious Courts throughout Central Kalimantan, followed by the Implementation of Accrual-Based Government Accounting Standards (coefficient 0.264), Quality of Human Resources (coefficient 0.251), and Utilization of Information Technology (coefficient 0.236). The adjusted R-squared value of 0.782 indicates that 78.2% of the variation in financial report quality can be explained by these factors, affirming the model's explanatory power. The mean values of the variables indicate that all aspects, including Financial Report Quality, Internal Control System, Human Resource Quality, Utilization of Information Technology, and Implementation of Accrual-Based Government Accounting Standards, have been implemented well.